Evidence for a Saponin Biosynthesis Pathway in the Body Wall of the Commercially Significant Sea Cucumber Holothuria scabra - Mitu, Shahida Akter (Mar Drugs, 2017)
The sea cucumber (phylum Echinodermata) body wall is the first line of defense and is well known for its production of secondary metabolites; including vitamins and triterpenoid glycoside saponins that have important ecological functions and potential benefits to human health. The genes involved in the various biosynthetic pathways are unknown. To gain insight into these pathways in an echinoderm, we performed a comparative transcriptome analysis and functional annotation of the body wall and the radial nerve of the sea cucumber Holothuria scabra; to define genes associated with body wall metabolic functioning and secondary metabolite biosynthesis. We show that genes related to signal transduction mechanisms were more highly represented in the H. scabra body wall, including genes encoding enzymes involved in energy production. Eight of the core triterpenoid biosynthesis enzymes were found, however, the identity of the saponin specific biosynthetic pathway enzymes remains unknown. We confirm the body wall release of at least three different triterpenoid saponins using solid phase extraction followed by ultra-high-pressure liquid chromatography-quadrupole time of flight-mass spectrometry. The resource we have established will help to guide future research to explore secondary metabolite biosynthesis in the sea cucumber.